THE ADULTERY OF EMMA ROUAULTY IN GUSTAVE FLAUBERT’S MADAME BOVARY: A PSYCHOANALYTIC APPROACH - KUSUMAWATI , NANIK WIDIYA (2007)
The study aims at finding the motives that encourage Emma, the major character, to commit adultery in Gustave Flaubert’s Madame Bovary. The object of research is the novel entitled Madame Bovary, by Gustave Flaubert. The researchers uses Psychoanalytic approach focusing on Sigmund Freud’s psychoanalytic theory of motivation in analyzing the adultery of Emma Renault. Therefore, the study analyses the novel in terms of its structural elements and based on psychoanalytic theory. The study belongs to a qualitative study in which the writer uses two data sources. The primary data source is the novel Madame Bovary itself , meanwhile the secondary one is any literature related to the study. From the result of analysis, it can be drawn some conclusion. Firstly, the structural elements of the novel present a good unity. It consists of exposition, complication, climax and resolution. Flaubert takes the theme that adultery is not good, we must learn to faithful with our couple. Secondly, it tells that Emma’s motivation of committing adultery is dealing with her disappointment to her marriage life. Being thirst for sexual satisfaction and love from romantic man forces her to commit adultery.